2018
DOI: 10.1016/j.fas.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Gait analysis and functional outcome in patients after Lisfranc injury treatment

Abstract: This study showed that patients treated for Lisfranc injury had significantly lower walking speed and significantly lower flexion/extension in the midfoot than healthy subjects. The ROM in these patients was significantly correlated with PROM, but not with radiographic quality of reduction. Most important satisfaction predictors were BMI, ROM in the sagittal plane during the push-off phase and fracture stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…The use of trans articular screws or a primary arthrodesis has never been considered in knee or shoulder ligament injuries, and, in that way, why should they be considered in a joint with movement and with an important biomechanical property in the foot? After Lisfranc injuries, patients have altered gait compared with healthy subjects (9). When gait analysis is performed in patients who have had a Lisfranc stabilization with trans articular screws or arthrodesis, they show a significantly lower walking speed and significantly decreased flexion/ extension in the midfoot during push-off phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of trans articular screws or a primary arthrodesis has never been considered in knee or shoulder ligament injuries, and, in that way, why should they be considered in a joint with movement and with an important biomechanical property in the foot? After Lisfranc injuries, patients have altered gait compared with healthy subjects (9). When gait analysis is performed in patients who have had a Lisfranc stabilization with trans articular screws or arthrodesis, they show a significantly lower walking speed and significantly decreased flexion/ extension in the midfoot during push-off phase.…”
Section: Discussionmentioning
confidence: 99%
“…This could indicate that in the post-operative phase a high flexion-extension motion is important for patient satisfaction. Even in patients where hardware was removed before gait analysis, they still presented a non-functional gait (9,20). This last fact highlights the need of finding a reliable, functional and non-rigid reconstruction of midfoot injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant differences were found between the two groups in terms of joint balance in the midfoot during the take-off phase (push-off) in the sagittal plane (flexion/extension). 30…”
Section: Resultsmentioning
confidence: 99%
“…The investigators found a significantly lower walking speed and a significantly decreased range of motion of the midfoot during the push-off phase. 16…”
Section: Introductionmentioning
confidence: 99%